2012
DOI: 10.1371/journal.pone.0042330
|View full text |Cite
|
Sign up to set email alerts
|

Serum Levels of Choline-Containing Compounds Are Associated with Aerobic Fitness Level: The HUNT-Study

Abstract: BackgroundCardiovascular disease (CVD) is a leading cause of death worldwide, and the number of people at risk is continuously growing. New methods for early risk prediction are therefore needed to actuate prevention strategies before the individuals are diagnosed with CVD. Several studies report that aerobic fitness level, measured as maximal oxygen uptake (VO2max), is the single best predictor of future CVD mortality in healthy people. Based on this, we wanted to study differences between healthy individuals… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
34
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 23 publications
(39 citation statements)
references
References 44 publications
5
34
0
Order By: Relevance
“…Other explanation for the high levels of serum choline in TA patients may be release of choline from damaged/injured arteries in agreement with previous reports showing choline release from ischemic tissues into the blood stream in patients with severe repetitive arrhythmias and hemodynamiccompromises [59][60][61]. High serum levels of free choline have also been associated with an increased prevalence of the metabolic syndrome (a cluster of risk factors of cardiovascular diseases)62 and in healthy individuals with a low aerobic fitness (a kind of hypoxia) 57,58,63. As TA patients fulfil various criteria i.e.…”
supporting
confidence: 90%
“…Other explanation for the high levels of serum choline in TA patients may be release of choline from damaged/injured arteries in agreement with previous reports showing choline release from ischemic tissues into the blood stream in patients with severe repetitive arrhythmias and hemodynamiccompromises [59][60][61]. High serum levels of free choline have also been associated with an increased prevalence of the metabolic syndrome (a cluster of risk factors of cardiovascular diseases)62 and in healthy individuals with a low aerobic fitness (a kind of hypoxia) 57,58,63. As TA patients fulfil various criteria i.e.…”
supporting
confidence: 90%
“…A further study comparing distinct categorised groups of low and high fitness demonstrated that the low fitness group had lower levels of phosphatidylcholine and increased free choline (approximately 1.5-fold, p = 0.017, Bye et al, 2012). Circulating free choline has recently been implicated in cardiovascular disease (Wang et al, 2014) and is known to be metabolised by the gut microbiome to form an intermediary in the production of trimethylamine N-oxide (Wang et al, 2011), a small molecule metabolite associated with reduced survival in conditions such as heart failure and myocardial infarction (Suzuki, Heaney, Bhandari, Jones, & Ng, 2016;Tang et al, 2014).…”
Section: Current Investigations In Sport and Exercise Sciencementioning
confidence: 96%
“…The samples were slowly thawed at room temperature. Aliquots of 300 µL were mixed with equal amount of buffer solution as described elsewhere 8 . Samples were then transferred to highquality 5 mm MR tubes.…”
Section: Metabolic Profilingmentioning
confidence: 99%
“…Metabolic profiling of biofluids can provide an extensive view of changes in endogenous metabolites in monitoring cellular responses to perturbations such as normal physiology, diseases and drug treatments [4][5][6][7][8] . Metabolomics have been successfully used in the detection of biomarkers 4 associated with various clinical conditions such as detection of ovarian cancers [9][10][11][12][13] and in differentiating benign and malignant ascites 14 .…”
Section: Introductionmentioning
confidence: 99%